Konsep Pendidikan Berkemajuan (Analisis Metode Pembelajaran di SMP Muhammadiyah 57 Medan) - Dede Maharani; Zahroni fatwa; Febi Anita Sari; Hasrian Rudi Setiawan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
The education concept initiated by K.H Ahmad Dahlan has given birth to great ideas and is a reference in managing education in Indonesia. The aim of this research is the concept of K.H Ahmad Dahlan's educational thought, namely: (1) Pragmatic; (2) Update; (3) Independence; (4) Balance; (5) Integration; (6) Openness; (7) Leadership; (8) Concern; (9) Certainty; (10) Justice. This research was conducted at SMP Muhammadiyah 57 Medan using qualitative descriptive methods. The results of the research show that the learning methods used at SMP Muhammadiyah 57 Medan are in accordance with the concept of progressive education initiated by K.H Ahmad Dahlan. In brief, this article discusses the concept of progressive education initiated by K.H Ahmad Dahlan and its relevance to education management in Indonesia. The research was conducted at SMP Muhammadiyah 57 Medan using qualitative descriptive methods, and the results showed that the learning methods used at the school were in line with the concept of progressive education.